2013
DOI: 10.1371/journal.pone.0077895
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose Stromal Cells (ASC) for the Regeneration of Injured Cartilage Display Genetic Stability after In Vitro Culture Expansion

Abstract: Mesenchymal stromal cells are emerging as an extremely promising therapeutic agent for tissue regeneration due to their multi-potency, immune-modulation and secretome activities, but safety remains one of the main concerns, particularly when in vitro manipulation, such as cell expansion, is performed before clinical application. Indeed, it is well documented that in vitro expansion reduces replicative potential and some multi-potency and promotes cell senescence. Furthermore, during in vitro aging there is a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 84 publications
4
45
0
Order By: Relevance
“…ASCs exhibit higher genetic stability in long-term culture compared to BM-MSCs (Dahl et al 2008; Neri et al 2013). However, research carried out by at least one research group has shown that karyotype irregularities occur with a frequency of >30 %.…”
Section: Impact Of Culture On Senescence and Genetic Stability Of Ascsmentioning
confidence: 99%
“…ASCs exhibit higher genetic stability in long-term culture compared to BM-MSCs (Dahl et al 2008; Neri et al 2013). However, research carried out by at least one research group has shown that karyotype irregularities occur with a frequency of >30 %.…”
Section: Impact Of Culture On Senescence and Genetic Stability Of Ascsmentioning
confidence: 99%
“…The demonstration of the absence of genetic instability by karyotype analysis should be assessed by molecular [54] or conventional methods (G banding). At least 20 metaphases should be analysed, and in the presence of aberrations, 20 more metaphases are requested, as defined by the General Guidelines and Quality Assurance for Cytogenetics [47,[55][56].…”
Section: Karyotypementioning
confidence: 99%
“…The most often applied multipotent stem cells, both as a research tool and in clinical trials, are those isolated from bone marrow multipotent stem cells (BMMSCs) and of adipose origin multipotent stem cells (ASCs). Although both of the above mentioned stem cell populations exhibit many similarities, ASCs are a potentially better candidate for regenerative medicine [2,[4][5][6]. This is because of their high viability and ease of obtaining in large quantities with little donor site related complications or patient discomfort.…”
Section: Introductionmentioning
confidence: 99%